2012
DOI: 10.1212/wnl.0b013e3182518328
|View full text |Cite
|
Sign up to set email alerts
|

LGI1 microdeletion in autosomal dominant lateral temporal epilepsy

Abstract: This is the first microdeletion affecting LGI1 identified in ADLTE. Families with ADLTE in which no point mutations are revealed by direct exon sequencing should be screened for possible genomic deletion mutations by CNV analysis or other appropriate methods. Overall, CNV analysis of multiplex families may be useful for identifying microdeletions in novel disease genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…In our series of 35 Italian ADLTE families (33 described in Michelucci et al, 2013, and 2 in this study), we identified 12 LGI1-mutated families (34%), each segregating a different mutation. Ten of 35 families (28%) segregated LGI1 point mutations (9 reviewed in Michelucci et al, 2013, and 1 described in this study), whereas 2 (6%) had microdeletions (Fanciulli et al, 2012;and present study). This ratio (5:1) between point mutations and gene rearrangements is in line with that found in other genes for Mendelian disorders (Botstein and Risch, 2003).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In our series of 35 Italian ADLTE families (33 described in Michelucci et al, 2013, and 2 in this study), we identified 12 LGI1-mutated families (34%), each segregating a different mutation. Ten of 35 families (28%) segregated LGI1 point mutations (9 reviewed in Michelucci et al, 2013, and 1 described in this study), whereas 2 (6%) had microdeletions (Fanciulli et al, 2012;and present study). This ratio (5:1) between point mutations and gene rearrangements is in line with that found in other genes for Mendelian disorders (Botstein and Risch, 2003).…”
Section: Discussionsupporting
confidence: 49%
“…De novo LGI1 mutations have been detected in a small proportion (about 1%) of sporadic lateral temporal epilepsy (LTE) patients (Bisulli et al, 2004a;Michelucci et al, 2007). Nearly all LGI1 mutations are point mutations, either nonsynonymous or splice-site mutations or short indels, distributed along the gene length Ho et al, 2012), and only a single microdeletion spanning the first four exons has been reported (Fanciulli et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…High‐density single nucleotide polymorphism (SNP) arrays that include nonpolymorphic probes optimized for copy number measurements can detect CNVs as small as 10 kb . By using these high‐density SNP platforms, we recently identified the first LGI1 microdeletion associated with ADLTE …”
mentioning
confidence: 99%
“…The 12 LGI1 mutated families have been described in detail elsewhere [2], [5], [7], [8], [9], [10], [11], [12], [13] whereas the 7 pedigrees with RELN mutations have been reported limited only to the genetic findings [6].…”
Section: Methodsmentioning
confidence: 99%